Energy efficiency in small districts: Dynamic simulation and technoeconomic analysis. (15th September 2020) - Calise, Francesco; Cappiello, Francesco Liberato; Dentice d'Accadia, Massimo; Vicidomini, Maria
Highlights: Dynamic tool for the evaluation of the energy demand of a residential district. Comparison of several measures reducing residential district energy consumption. Performance evaluation of several heat pump technologies coupled with photovoltaic. The proposed layouts achieve promising energy environmental and economic performances. The use of air-to-air heat pumps for space heating is extremely profitable. Abstract: In European Union Countries, local authorities have developed their own Sustainable Energy Action Plan aiming at planning the urban strategies to achieve the European Union and national 2020 energy targets. This document is used for detecting and deploying the energy measures which each municipality should adopt in order to reduce the environmental impact of the municipality activities. Further efforts are expected to define the strategies for achieving 2050 goals. In this framework, this work deals with the dynamic estimation energy saving actions for small districts located in different Italian weather zones (Naples and Turin, located in South and North Italy, respectively). The data of the Sustainable Energy Action Plan were used to develop suitable dynamic models, implemented in TRNSYS environment, including different buildings of selected districts. In particular, all the buildings were modelled by means of the Type 56 of TRNSYS, coupled to the Google SketchUp TRNSYS3d plug-in. By means of Type 56, it is possible to take into account and simulate the buildings geometry, envelope, windows, lighting, machineries heat gains schedule as well as the buildings users' occupation and activity. Given the loads, several energy efficient renovation alternatives based on the adoption of air-to-air conventional and carbon dioxide heat pumps, evacuated thermal collectors and photovoltaic panels, as well as the envelope renovation of all the public and private buildings of the district, are proposed and compared. Results, obtained by detailed dynamic energy and environmental analyses, can be used as guidelines for the local authorities to implement suitable energy efficiency actions of existing buildings in order to reduce both the thermal energy and carbon dioxide emissions due to the building space heating/cooling, domestic hot water and electricity. The proposed renewable layout for Naples case study achieves a primary energy savings of 58% with a payback period of 4 years. The renewable layout for Turin case study achieves a primary energy savings of 76% with a payback period of 10.6 years.